The Cost and Benefits of Employee Training: Analyzing ROI in Human Resources - Sihombing, Sarinah; Setiawati, Aswanti; Sitanggang, Rohana; Thabah, Asep Ali (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research investigates the multifaceted dimensions of employee training and its implications for organizational performance. Employing a qualitative approach, the study aims to deepen our understanding of training effectiveness and Return on Investment (ROI) analysis in Human Resources (HR). The research design involves a systematic literature review from peer-reviewed journals and reputable databases, focusing on key themes such as training definitions, methodologies, outcomes, and measurement techniques. Thematic analysis of the collected literature reveals several significant findings. Firstly, employee training is essential for enhancing individual competencies and aligning organizational goals. Secondly, training initiatives contribute to organizational culture, innovation, and talent development. Thirdly, a strategic training design and evaluation approach enhances organizational performance and competitiveness. Fourthly, innovative training methodologies, such as personalized learning and immersive experiences, offer promising avenues for optimizing training effectiveness. Lastly, integrating training initiatives with broader HR strategies, such as talent management and performance management, enhances their impact on organizational success. The study underscores the need for future research to explore the longitudinal effects of training interventions and advance methodologies for ROI analysis.